Amyotrophic lateral sclerosis: The complement and inflammatory hypothesis. (October 2018) - Kjældgaard, Anne-Lene; Pilely, Katrine; Olsen, Karsten Skovgaard; Pedersen, Stephen Wørlich; Lauritsen, Anne Øberg; Møller, Kirsten; Garred, Peter
Highlights: Complement proteins in neuromuscular junctions as first sign of pathology implicate systemic innate immune system in the pathophysiology of ALS. Increasing complement activation in spinal cord during progression suggests that the complement system contributes to the pathogenesis of ALS. Cross-talk between microglia and motor neurons via imbalanced local complement seems to exacerbate the destruction of ALS motor neurons. Cytotoxicity in plasma/serum from ALS patients indicates systemic involvement of the innate immune system. Abstract: Amyotrophic lateral sclerosis (ALS) is a devastating, neurodegenerative motor neuron disease. The aetiology of ALS remains an enigma which hinders the design of an effective treatment to prevent, postpone, or reverse the pathophysiological changes occurring during the aggressive progression of this disease. During the last decade, basic research within the innate immune system, and in particular the complement system, has revealed new, important roles of the innate immune system during development, homeostasis, and ageing within as well as outside the central nervous system. Several lines of evidence indicate that aberrant activation of the complement system locally in the central nervous system as well as systemically may be involved in the pathophysiology of ALS. This exciting new knowledge could point towards the innate immune system as a potential target of medical intervention in ALS. Recently, the historic perception of ALS as a central neurodegenerative disease has been challenged due to the significant amount of evidence of a dying-back mechanism causing the selective destruction of the motor neurons, indicating that disease onset occurs outside the borders of the blood-brain-barrier. This review addresses the function of the innate immune system during ALS. We emphasize the role of the complement system and specifically suggest the involvement of ficolin-3 from the lectin pathway in the pathophysiology of ALS.